Persian literature course in the undergraduate medical curriculum - Khoshgoftar, Zohreh; Yaghmaei, Minoo; Nazari, Leila (Student Research in Translational Medicine, 2021)
A serious criticism of contemporary medicine is that it is dehumanized, meaning that it ignores the patient and his/her experiences, values, and priorities as an individual human and only seeks treatment based on the latest findings in the biomedical sciences. To modify and improve this situation, the field of "medical humanities" was formed, which seeks to include human considerations in clinical practice. One of the important domains of the field of “medical humanities” is "Literature and Medicine". Literature and medicine are now taught in medical schools at all undergraduate (both in basic sciences and clinical periods) and residency levels. Broadly speaking, the reasons for this implementation are threefold. The first concerns the patient: such courses teach physicians how to listen more wisely to their patients’ narratives and how to emphasize with the patient’s and family members’ points of view on the experience of illness and treatment. The second reason concerns the physician: Reading literature enhances personal awareness and fosters the habit of self-scrutiny. The third concerns ethics: literature and literary skills empower physicians to think both empathetically and critically about moral issues and dilemmas in daily clinical practice. By reviewing the texts in the field of literature and medicine, we come across various educational programs in medical schools around the world. One of the courses in the Doctor of Medicine (MD) curriculum of Iran is Persian literature (code: 16) which three theoretical units (51 hours). This course, for which a lesson plan has not been designed in the curriculum, is usually offered to students in one of the first year. Since the Persian literature course is in the general courses section, like other courses in this section such as philosophy of ethics, Islamic ethics, and familiarity with the Constitution of the Islamic Republic of Iran, – Cont.